Neonatal diabetes caused by the heterozygous Pro1198Leu mutation in the ABCC8 gene in a male infant: 6‐year clinical course. Issue 2 (27th August 2019) - Uraki, Shinsuke; Furuta, Hiroto; Miyawaki, Masakazu; Matsutani, Norihiko; Shima, Yuko; Iwamoto, Miki; Matsuno, Shohei; Morita, Shuhei; Furuta, Machi; Doi, Asako; Iwakura, Hiroshi; Ariyasu, Hiroyuki; et al.
Abstract: Neonatal diabetes is a rare disease, often caused by a monogenic abnormality. A male infant patient developed diabetic ketoacidosis at 2 months‐of‐age due to the heterozygous ABCC8 gene mutation (p.Pro1198Leu). After genetic diagnosis, insulin therapy was successfully transitioned to oral sulfonylurea therapy. For >6 years, oral sulfonylurea therapy has been safe and effective, and the required amount of sulfonylureas has progressively decreased. The mutation was transmitted in an autosomal‐dominant fashion across three generations of his family, but the severity of diabetes varied among members from neonatal diabetes to mild diabetes. One family member had normal glucose tolerance despite having the mutation. This case presentation could help in the understanding of neonatal diabetes caused by the ABCC8 gene mutation. Abstract : A male infant developed diabetic ketoacidosis (DKA) at 2 months‐of‐age due to the heterozygous ABCC8 gene mutation (p.Pro1198Leu). After genetic diagnosis, insulin therapy was successfully transitioned to oral sulfonylurea therapy. After that, for >6 years, oral sulfonylurea therapy has been safe and effective, and the required amount of sulfonylureas has progressively decreased.